Forefoot and heel take-off strategies result in different distribution of lower extremity work during landings - Dæhlin, T. E.; Chiu, L. Z. F. (Journal of Sports Sciences, 2019)
Previous research suggests that landing mechanics may be affected by the mechanics of the preceding jump take-off. The purpose of the present study was to investigate whether jump take-off mechanics influence the subsequent landing mechanics. Female volleyball (n = 17) and ice hockey (n = 19) players performed maximal vertical jumps with forefoot and heel take-off strategies. During forefoot and heel jumps, participants were instructed to shift their weight to their forefoot or heel, respectively, and push through this portion of the foot throughout the jump. Jump mechanics were examined using 3D motion analysis, where lower extremity net joint moment (NJM) work, NJM, and segment angles were compared between forefoot and heel jumps using multivariate ANOVA. During jump take-off, participants performed more positive ankle plantar flexor and knee extensor NJM work in forefoot compared to heel jumps (P < 0.05). From initial foot contact to foot flat, participants performed more negative ankle plantar flexor and hip extensor NJM work during heel compared to forefoot jumps (P < 0.05). The present results demonstrate that using a heel take-off strategy results in a different distribution of lower extremity NJM work and NJM during landing compared to landings following forefoot jumps.